A Survey of Functional Status to Support CommunityChoice Rate Setting and Program Assessments - Tucker, Anthony M. (Center for Health Program Development and Policy, 2006)
The Hilltop Institute (as the Center for Health Program Development and Management) conducted a telephone survey of 2,100 community-dwelling Maryland Medicaid beneficiaries as the first phase of a broader research agenda to explore how functional status, as measured by activities of daily living (ADLs), is related to resource use over time, as well as how such measures might be used for rate setting and performance assessment for CommunityChoice and other integrated managed long-term care programs.
Keywords: survey of functional status; community choice-eligible population